Anthropogenic effects on bacterial diversity and function along a river‐to‐estuary gradient in Northwest Greece revealed by metagenomics. (30th April 2016) - Meziti, Alexandra; Tsementzi, Despina; Ar. Kormas, Konstantinos; Karayanni, Hera; Konstantinidis, Konstantinos T.
Summary: Studies assessing the effects of anthropogenic inputs on the taxonomic and functional diversity of bacterioplankton communities in lotic ecosystems are limited. Here, we applied 16S rRNA gene amplicon and whole‐genome shotgun sequencing to examine the microbial diversity in samples from the Kalamas River (Northwest Greece), a mid‐size river that runs through agricultural and NATURA‐protected areas, but also receives urban sewage from a large city through a manmade ditch. Samples from three different locations between the exit of the ditch and the estuary, during three different months showed that temporal differences of taxonomic and functional diversity were more pronounced than spatial ones, and <1% of total taxa were shared among all samples, revealing a highly dynamic ecosystem. Comparisons of gene diversity with other aquatic habitats showed that only the high flow winter samples resembled more to freshwater environments while samples during the decreased water flow months were dominated by sewage inputs and soil‐related organisms. Notably, microbial human gut signals were detectable over background freshwater and soil/runoff related signals, even at tens of kilometers downstream the city. These findings revealed the significance of allochthonous inputs on the composition and dynamics of river bacterial communities, and highlighted the potential of metagenomics for source tracking purposes.